Issue Information. (26th April 2019) - Unknown
Abstract : Anterior segment dysgenesis (ASDG) includes heterogeneous disorders, which primarily affect the anterior segment of the eye. PITX3, FOXE3, FOXC1, PITX2, and PAX6 are representative causal genes for ASDG types 1 to 5, respectively. Further details can be seen in the Invited Review Article by Ohuchi et al. in this issue. Abstract : Anterior segment dysgenesis (ASDG) includes heterogeneous disorders, which primarily affect the anterior segment of the eye. PITX3, FOXE3, FOXC1, PITX2, and PAX6 are representative causal genes for ASDG types 1 to 5, respectively. Further details can be seen in the Invited Review Article by Ohuchi et al. in this issue.